Physiochemical analysis of drinking water in high and low crude oil-producing communities in the Niger Delta Region, Nigeria - Luke, Anwuri; Tobin-West, Charles I.; Ofuru, Vitalis O.; Owhonda, Golden; Igwele, Pabara N. (International Journal Of Community Medicine And Public Health, 2023)
Background: Access to potable water is a human right that plays a significant role in maintaining health and sanitation. Its limited supply in oil-producing areas has been variously linked to diverse pollutants in crude oil-producing communities, in Nigeria’s Niger Delta region. This cross-sectional study analysed and compared the physico-chemistry of drinking water sources in high and low crude oil-producing communities in the Niger Delta region between January to February 2023. Methods: Water samples were collected from a total of 28 samples from geo-referenced points in 10 communities. Analysis was done using the approved APHA and ASTM methods and assessed based on the recommended World Health Organization (WHO) permissible limits of detection for water quality. Data were analyzed using the statistical package for social science (SPSS) version-26. Test of significance and associations were set at p<0.05 and 95% confidence level. Results: There were significant differences in the mean concentrations of water alkalinity, chromium (Cr), barium (Ba), total petroleum hydrocarbons (TPH), polyaromatic hydrocarbons (PAH), and TOG in water sources of the high and low oil-producing communities. Other mean concentrations of the analysed physicochemical parameters were found to be within normal limits for pH, salinity, turbidity, EC, total dissolved solids (TDS), total suspended solid (TSS), DO, and BOD, below the limit for alkalinity, chemical oxygen demand (COD), nitrate (NO3), ammonia (NH3), sulphate (SO4), bicarbonates (HCO3), chromium (Cr), copper (Cu), iron (Fe), TPH and above recommended limits for temperature, PAH and TOG. Conclusions: The study showed that both high and low oil-producing communities had contaminated ground and surface water sources, although the high oil-producing areas were much more polluted. It is, therefore, necessary to enhance the national oil pollution regulatory mechanisms and remediation activities in heavily polluted sites to safeguard community water sources and protect human health.